Meningkatkan Minat Belajar Ekonomi Melalui Model Pembelajaran PjBL di SMAN 5 Palembang - rani; Siti Fatimah; Nani Yuliasti (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2024)
One of the key aspects in the educational process is interest in learning. Based on the results of the pre-research questionnaire on class X.3 students, it was found that on average students did not yet have an interest in studying economics. This research was conducted to increase students interest in studying economics in class X.3 through a project based learning model at SMA Negeri 5 Palembang. This research is a classroom action research carried out in three cycles. The type of data used is descriptive quantitative data. The subjects of this study were 38 students in class X.3. Based on the results of the study, in cycle I to cycle III it was 16.87% from the initial average in cycle I of 69.41% which had a moderate interest in learning category to 86.28% in cycle III which had a very high learning interest category. The application of the project based learning learning model is able to increase the interest in studying economics for class X.3 students of SMA Negeri 5 Palembang. Future research can be expected to use more recent theories regarding learning interest and PjBL.